-3y-12=-6

Simple and best practice solution for -3y-12=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3y-12=-6 equation:


Simplifying
-3y + -12 = -6

Reorder the terms:
-12 + -3y = -6

Solving
-12 + -3y = -6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -3y = -6 + 12

Combine like terms: -12 + 12 = 0
0 + -3y = -6 + 12
-3y = -6 + 12

Combine like terms: -6 + 12 = 6
-3y = 6

Divide each side by '-3'.
y = -2

Simplifying
y = -2

See similar equations:

| 12X-4y=9 | | 24y+60=-5-6 | | 6-6b+b+5=1-3b | | 28000+3000x=7000x+18000 | | 49x-27=2-1.5 | | -(4m-3)=-3(m-2) | | 28000+3000x=6000x+18000 | | 28000+3000x=8000x+18000 | | 28000+3000x=5000x+18000 | | 28000+3000x=1600x+18000 | | 3+6x-2x=35 | | 28000+3000x=1000x+18000 | | 14x+7y=0 | | 28000+3000x=200x+18000 | | 4(2x-1)=68 | | 28000+3000x=3000x+18000 | | 7x+6(x-4)=x | | 28000+3000x=2500x+18000 | | N-4n+2=20 | | 28000+3000x=2000x+18000 | | 28000+3000x=3500x+18000 | | 4.7x+6(x-4)=x | | 8(t-7)-3(t-4)=6(t-7)+8 | | (7P+1)X^2+(5P-1)X+P=1 | | -6(m-6)=-8(m-1) | | 5-3(x-4)=16 | | f(x+1)=2x^2+3x-4 | | 4(2n-3)=20 | | 25.50+6p=45 | | 25x^2-30x-7=-7 | | 5r=53 | | 2x+105+2x+70+x+8+105=360 |

Equations solver categories